Modeling of novel zigbee/IEEE802.15.4 MAC protocol for SCADA low voltage smart grid distribution systems - Shabani, Hikma; Ahmed, Musse Mohamud; Khan, Sheroz; Hameed, Shihab A.; Habaebi, Mohamed Hadi (2014)
The loss of the integrity and/or availability of data has the potential to diversely affect power utility core operations. Supervisory Control and Data Acquisition (SCADA) system is a computer system for collecting and analyzing data in almost real-time fashion for monitoring purposes. SCADA refers to the combination of telemetry and data acquisition. Communication plays, thus, a core role in SCADA systems. The use of wireless sensor network (WSN) can, however, lead to a more flexible and powerful protection scenarios than the current used wired sensor. Merit to Zigbee/IEEE802.15.4 as one of the promising WSN standards due to its low cost of deployment, low power, low data rate, short range, simplicity and free licensed spectrum. While a beacon-enabled mode is adopted for energy efficiency operations with a multi-hop mesh network built up for large coverage, IEEE802.15.4 standard does not provide any mechanisms for a beacon-enabled mode in multi-hop mesh networks. Hence, in order to provide a real-time data exchange and thus, predict a real-time system control, a Novel Zigbee/IEEE802.15.4 MAC Protocol for SCADA system is modeled in this paper. The protocol performance is evaluated using NS-2 Simulation and the preliminary results are encouraging.